Factors Influencing the Adoption of Management Accounting Practices in Cameroon - Fidelis Akanga; Dominic Roberts (Goodwood Publishing, 2026)
Purpose: This study aims to identify the factors that influence the adoption of Merchant Advisory Panels (MAPs) by organizations in Cameroon (a former German, British, and French colony) and how MAPs can help organizations to be resilient to internal and external environments. Methodology: This study used a case study approach and data were collected using 20 in-depth interviews with managers and accountants of private sector organizations in Cameroon and document review. Results: There is a considerable disparity in the adoption of MAP by organizations operating in Cameroon due to colonial heritage. Organizations in the English-speaking regions consider professional accountants, in contrast to those in French Cameroon. Owing to external factors, such as the Anglophone crisis, government intervention through price regulation, and the COVID-19 pandemic, organizations have adopted innovative MAPs to help them stay resilient. Conclusions: MAP plays a key role in decision-making organizations. However, in the case of Cameroon, differences in the use of accounting professionals mean that there is no consistency in decision making. The government should enact legislations and provide support for organizations to use accounting professionals to benefit organizations. Limitations: This study is limited to a few organizations in the two regions of the country. This means that their perceptions and use of MAP might differ for other organizations facing different situations. Contributions: Management accounting is one of the techniques used by organizations to govern themselves and make good decisions. Therefore, understanding how these practices play in different socioeconomic, cultural, and political settings is of great importance. This is exactly what this research achieves.